Effect of the diet on lipid composition and liver histology of short snout seahorse Hippocampus hippocampus. (25th August 2015) - Segade, Á.; Robaina, L.; Novelli, B.; Otero‐Ferrer, F.; Molina Domínguez, L.
Abstract: Little is known about the nutritional requirements of ornamental fish and the effects which they may have on fish histology. Because of this, 45 young, captive‐bred seahorses (1.37 g ± 0.51) were randomly divided and put into fifteen, 35‐L, glass aquariums. Three experimental diets were tested in triplicate: live enriched Artemia (LEA); frozen enriched Artemia (FEA); and commercial Mysis (M). seahorses were fed twice daily, 6 days a week for 102 days throughout the experiment. The body weight and length of the seahorses were measured every 20 days, and at the end of the experiment, fish liver samples were taken for histological studies. Biochemical analyses of the diets and the seahorses fed on the experimental diets were recorded, and the differences in the total lipid content in each of the three diets were also observed, each reflecting their respective liver lipid content. seahorses fed with LEA treatment showed lipid vacuoles in the hepatocytes with nuclei displaced to the periphery. Similar results were also observed in FEA fed seahorses, but to a lesser extent. In contrast, the M fed seahorses were characterized by having livers with lower size hepatocytes and centrally located nuclei.